Targeted drug delivery of engineered mesenchymal stem/stromal-cell-derived exosomes in cardiovascular disease: recent trends and future perspectives - Pang, Jian-Liang; Shao, Hong; Xu, Xiao-Gang; Lin, Zhi-Wei; Chen, Xiao-Yi; Chen, Jin-Yang; Mou, Xiao-Zhou; Hu, Pei-Yang (Frontiers in Bioengineering and Biotechnology, 2024)
In recent years, stem cells and their secretomes, notably exosomes, have received considerable attention in biomedical applications. Exosomes are cellular secretomes used for intercellular communication. They perform the function of intercellular messengers by facilitating the transport of proteins, lipids, nucleic acids, and therapeutic substances. Their biocompatibility, minimal immunogenicity, targetability, stability, and engineerable characteristics have additionally led to their application as drug delivery vehicles. The therapeutic efficacy of exosomes can be improved through surface modification employing functional molecules, including aptamers, antibodies, and peptides. Given their potential as targeted delivery vehicles to enhance the efficiency of treatment while minimizing adverse effects, exosomes exhibit considerable promise. Stem cells are considered advantageous sources of exosomes due to their distinctive characteristics, including regenerative and self-renewal capabilities, which make them well-suited for transplantation into injured tissues, hence promoting tissue regeneration. However, there are notable obstacles that need to be addressed, including immune rejection and ethical problems. Exosomes produced from stem cells have been thoroughly studied as a cell-free strategy that avoids many of the difficulties involved with cell-based therapy for tissue regeneration and cancer treatment. This review provides an in-depth summary and analysis of the existing knowledge regarding exosomes, including their engineering and cardiovascular disease (CVD) treatment applications.